Inbetweenness: Transcultural Thinking in my Compositional Practice - Isaiah, Lee Chie Tsang (Malaysian Journal of Music, 2018)
This article explores the notion of ‘in-betweenness’ through transcultural thinking in my compositional practice. My thinking has been inspired by Tim Ingold’s philosophical idea of ‘wayfaring’ as a way to navigate processes by which insights emerge from collaborative investigations. 'Interbreathment’ is one of the earlier projects focusing on music and dance collaborations. Associated with a gong installation, this particular project explored a hybrid form of notation between musical and choreographical elements engaging with Chinese, as well as Malaysian indigenous cultural references (Kadazandusun) in which I sought a creative threshold for opening up new cultural dialogues to deepen my experience and understanding of the notions of entanglement and of how highly diverse elements can be unified through collaboration in my compositional work.